2016
DOI: 10.1002/jts.22099
|View full text |Cite|
|
Sign up to set email alerts
|

Disgusted by Sexual Abuse: Exploring the Association Between Disgust Sensitivity and Posttraumatic Stress Symptoms Among Mothers of Sexually Abused Children

Abstract: Nonoffending mothers of sexually abused children often exhibit high levels of posttraumatic stress (PTS) symptoms. Emerging evidence suggests that trait-like individual differences in sensitivity to disgust play a role in the development of PTS symptoms. One such individual difference, disgust sensitivity, has not been examined as far as we are aware among victims of secondary traumatic stress. The current study examined associations between disgust sensitivity and PTS symptoms among mothers of sexually abused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It is necessary for future work to examine the selectivity of the disgust-PTSD relationship to support this assertion. At present, very few studies have examined the differences in disgust domains for people with PTSD, and only one study specifically deals with PTSD stemming from sexual trauma (van Delft et al, 2016); even then, the trauma was vicarious (symptoms in nonoffending mothers of sexually abused children). Notably, this last study found a positive association between sexual disgust and PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary for future work to examine the selectivity of the disgust-PTSD relationship to support this assertion. At present, very few studies have examined the differences in disgust domains for people with PTSD, and only one study specifically deals with PTSD stemming from sexual trauma (van Delft et al, 2016); even then, the trauma was vicarious (symptoms in nonoffending mothers of sexually abused children). Notably, this last study found a positive association between sexual disgust and PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Engelhard et al (2011) found no correlation among any of the subscales of the Disgust Scale–Revised and PTSD symptoms, Arocho (2015) found a positive relationship between core disgust and PTSD symptoms. Findings for the TDDS are also contradictory: Pathogen disgust either has no relationship to PTSD (R. Ojserkis, personal communication, February 15, 2018; van Delft, Finkenauer, Tybur, & Lamers-Winkelman, 2016) or a positive relationship (Arocho, 2015), sexual disgust has either no relationship or a positive relationship to PTSD (R. Ojserkis, personal communication, 2017, and van Delft et al, 2016, respectively), and moral disgust either does not correlate or has a negative relationship with PTSD symptoms (Arocho, 2015; Ojserkis et al, 2014; van Delft et al, 2016).…”
Section: Disgust and Ptsdmentioning
confidence: 99%
“…Archives of Psychiatry and Psychotherapy, 2023; 4: [39][40][41][42][43][44][45][46][47][48][49][50] Disgust is a basic emotion characterized by the feeling of repulsion or intense disapproval of an object, person or event considered unclean, unpleasant or offensive. Disgust can be elicited by something perceived through the sense of sight, smell, taste, or touch, or vividly imagined [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most have been conducted in Western societies and concentrated on identifying the prevalence of mothers' beliefs, the support provided in the aftermath of the disclosure, and the factors that facilitated this support (for example, Coohey & O'Leary, 2008;Cyr et al, 2003Cyr et al, , 2014. Qualitative and quantitative studies conducted in South Africa (Masilo & Davhana-Maselesele, 2016) and the Netherlands (van Delft et al, 2016) have focused on mothers' PTS symptoms in response to the disclosure. In addition, most studies on mothers' responses and internal experiences have dealt primarily with the general population rather than minority groups (Haboush & Alyan, 2013;Sawrikar & Katz, 2017a), and on small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that American, Dutch, and Canadian mothers of child victims of sexual abuse experienced heightened levels of depression, anxiety, and post-traumatic stress disorder (PTSD) symptoms (Lewin & Bergin, 2001; Rakow et al, 2011; van Delft et al, 2016) and exhibited fewer maternal attachment behaviors (Lewin & Bergin, 2001). These reactions have been shown to impair mothers’ self-efficacy and parental perception (Johnson et al, 2014), and the natural mother–child bond, thus inevitably influencing how mothers cope and support their children (McCarthy et al, 2019; Rakow et al, 2011).…”
Section: Introductionmentioning
confidence: 99%